Analisis Faktor-faktor Yang Mempengaruhi Niat Pengguna Untuk Terus Menggunakan Aplikasi SatuSehat - Pakereng, Yumina Yuti; Setyawan, Didik; Sugiyarmasto, Sugiyarmasto (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2024)
Background: Various problems that occur in the SatuSehat app make user satisfaction and intention to continue using the app even lower. So research on factors that can increase user satisfaction to continue using the SatuSehat app needs to be done. Aims: The purpose of this research was to investigate the willingness to persist in using the SatuSehat app. This willingness is impacted by both satisfaction and awareness of health. Additionally, satisfaction and health awareness are affected by an intermediary variable known as expected confirmation. Expected confirmation, in turn, is influenced by three factors: privacy security, system quality, and accuracy. Methods: Information was collected via surveys given to the general population meeting specific criteria and having experience with the SatuSehat app. A total of 211 individuals were included in the sample, selected through purposive sampling. To assess the validity, Structural Equation Modeling (SEM) Analysis with the AMOS method was employed. Results: The data analysis findings in this study indicate that both satisfaction and health awareness positively influence the intention to persist in using the app. Furthermore, expected confirmation positively affects both satisfaction and health awareness. Privacy security, system quality, and accuracy positively affect expectation confirmation. Conclusion: Individual expectations that are confirmed through the use of the app increase individual satisfaction and perceived health awareness. The high privacy security and quality of the application system in accordance with individual expectations and perceptions provide expectations for individuals to continue using the app. The accurate health information provided by the app also creates individual expectations to continue using the app.